(untitled) (Abhat Journal, 2023)
There is no doubt that English language has become a gateway for better communication and employment opportunities. Given the importance of English language, many countries often introduce curricula reforms of improve the status of English language teaching in their school system. However, during the implementation, these reforms often fail to achieve the goals of those who initiated and planned these curricula reforms. This failure is often attributed to the lack of understanding the key concepts related to the process of curricula reforms. In this paper, I shed light on these key issues in an attempt to facilitate the process ELT curricula reforms. This paper has implications and useful messages for educational policy makers, curriculum development processes, and teacher education programs in English language teaching in particular, and in education in general.